Penerapan Pendekatan Pembelajaran Deep Learning dalam Pemahaman Perintah Beriman kepada Kitab-Kitab Allah SWT pada Pembelajaran Pendidikan Agama Islam - Rodhatul Jennah; Agisna Fadilawati; Mazrur (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to describe the application of the Deep Learning approach to improving fifth-grade students' understanding of the command to believe in the holy books of Allah SWT, as stated in Chapter 2 of the book